Self-governance and punishment: An experimental study among namibian forest users - Vollan, Bjoern; Proepper, Michael; Landmann, Andreas; Balafoutas, Loukas (Economic Development and Cultural Change, 2019)
We use a framed field experiment to assess resource harvesting behavior and its interaction with prosocial and antisocial punishment in the Kavango woodland savannah of Namibia. We implement two treatments, one with external, centralized punishment and one with internal, decentralized punishment. Our findings suggest that institution type matters, as internal punishment is a more effective regime to discipline high harvesters compared with external punishment. We find that antisocial punishment (i.e., the sanctioning of people who cooperate by free riders) happens frequently, partly as revenge and especially in ethnically heterogeneous groups, but ultimately does not prevent cooperative self-governance.
Created from Fastlane, Scopus look-up